Internet and Indonesian EFL Teaching Profession - Susanti, Ani (Universitas Ahmad Dahlan, 2014)
AbstractThe integration of internet in education has been a global phenomenon.Â For EFL teachers, the use of internet is potential not only for classroom teaching and learning but also for professional learning. Warschauer et al (2000) claimed that internet for English teaching deals with ALIVE (Authenticity, Literacy, Interaction, Vitality and Empowerment).This qualitative research used guided questions to interview as many as 21 EFL teachers from junior high schools, senior high schools, English courses, and universities. The guided questions are designed to answer these research questions: What internet resources do Indonesian EFL teachers use for their professional learning and classroom teaching? How do they use the resources for both purposes? Why do and donât they use the resources for both purposes? The interview notes were then coded and categorized, then discussed.Â While it was portrayed from the findings that Indonesian EFL teachers believe in the benefits of internet for their profession; these beliefs do not generally affect their practices in using internet to enhance their teaching profession. It is recommended to guide Indonesian EFL teachers to optimize the usage of internet resources to enrich learning and to succeed teaching.Â Â